Factors Associated with Open Defecation Behavior in Communities in Wakeakea Village, Central Buton Regency - Wa Ode Nurhidayati; L M Zainul (Miracle Journal of Public Health, 2023)
The issue of sanitation is one of the world's major concerns. The World Health Organization (WHO) explains that sanitation is an effort to control all factors of the human physical environment that will cause things that are detrimental to physical development, health, and endurance Regarding open defecation, Data from the World Health Organization (WHO) in 2020, states that Indonesia is the second largest country in the world that still practices defecation amounting to 9.36% or around 25 million people, Indonesia is ranked second or in practice below India. The purpose of this study is to determine the factors of open defecation behavior in the Wakeakea community in the working area of the Rahia Health Center, Central Buton Regency in 2022. This type of research is quantitative with Cross Sectional design The population of this study is heads of families or wives in Wakeakaea Village, Gu District, totaling 246 households. The sampling technique uses total sampling. Data analysis was conducted univariate and bivariate The results showed that latrine ownership (p-value = 0.000), mileage (p-value = 0.000), and attitude (p-value = 0.000) had a significant relationship with defecation behavior. Advice to community leaders and related agencies to carry out community empowerment as a promotional effort related to the provision of healthy and well-behaved latrines not to defecate.